A VON BERTALANFFY MODEL WITH RESPONSE PLATEAU TO DESCRIBE GROWTH CURVES OF BEEF CATTLE - SANTANA, Tânia Jussara Silva; SCALON, João Domingos; BITTENCOURT, Thereza Cristina Calmon; SANTANA, Azly Santos Amorin de (Brazilian Journal of Biometrics, 2016)
Segmented models can be used to study the growth curve of animals whenever there is a situation where you need to use a function given by different laws in order to capture significant changes during the growth process. The first part of the model is given by a linear or non-linear function up to a given value. From that value, the function is a constant called plateau response. The most commonly used functions for the first part of the model are: linear, quadratic polynomial and exponential. The aim of this work was to propose the non-linear Von Bertalanffy’s model with response plateau to describe growth curves of beef cattle. This model was fit in weight data of Nelore cows from different regions of Brazil. The data was collected in eight times, between 1 and 600 days from birth, by the Brazilian Association of Zebu Breeders (ABCZ). The proposed model was compared, statistically, to the models most cited in the literature. The results showed that the von Bertalanffy’s model with response plateau provided better fit than the other response plateau models for the study of growth curves of Nellore cows.